KEEFEKTIFAN PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER UNTUK MENGEMBANGKAN KETERAMPILAN SOSIAL SISWA SD - Fajriyah, Khusnul (MALIH PEDDAS, 2014)
The role of elementary education is aimed to set the basis of intelligence, knowledge, personality, moral and skill to have a self-reliant life and also to continue the study to the next levels. The subjects or materials that the students received in elementary education have very significant influence to their next level education. Social skills are one of the curricular goals of Social Science that can be further developed throughout NHT cooperative learning. The aim of this research is to describe the process of NHT cooperative learning in social science material of Social Problems as well as reviewing its effectiveness in improving students social skills. This research is carried out in accordance with experimental research design which takes the fourth grade elementary students at Candisari District, Semarang as the population. The sampling method applies cluster sampling. The result of the research reveals that NHT cooperative learning is effective. This is shown by the result of social skill difference test between experiment group and control group where the value of tcal is 5.003 while on Î± = 5% and df= 116 the value of t(0.95)(116) is 1.66. This means that students social skill at experiment group is much better compared to control group. The students result difference test between experiment group and control group reveals that the value tcal is 2.116 while on Î± = 5% and df= 116 the value of t(0.95)(116) is 1.66. This means that students result at experiment group is much better compared to control group.Â The proportion of studentsâ mastery at experiment group has reached classical mastery which is 87%.